A REVIEW ON PASCHATA KARMA OF AHARA AND ITS EFFECT ON POSTPRANDIAL GLYCAEMIA W.S.R. SATAPADA GAMANA - Sadaf Ahmed; Ankita; Medha Kulkarni; Shivakumar S. Harti (International Journal of Ayurveda and Pharma Research, 2020)
Over the past several decades, the physical activities and fitness of Indian’s have significantly decreased which results in expand of non-communicable diseases where Diabetes is most common. Regular physical activity is accepted widely as an effective preventable measure for a variety of health risks as it helps in regulating blood glucose and other Physiological effects. Proper utilization of Glucose is very important. Limited instruction is available for post meal Procedure andabout physical activitywhich affects postprandial glycaemia. In this regard the present study is taken to find out the post dietary activities mentioned in Ayuveda and contemporary science. Study also implies that there is extensive scope of scientific research in this field in order to justify the textual references and to generate the data.